THE LINGERING INFLUENCE OF MEDIEVAL PRACTICES. - de Roover, Raymond (The Accounting Review, 1943)
Banks of deposit, managed by local moneychangers, existed in Venice, Florence, Genoa, Barcelona, Bruges, and probably in Antwerp and Paris. After 1400, there was a municipal bank in Barcelona, but the private banks continued to exist beside the new institution, and attempts to drive them out of business were un-successful. In Valencia also, a municipal bank was created but it failed to prosper and was dissolved after a few years. As a result of the use of oral orders in lieu of written checks, banking practices and accounting procedure were quite different from what they are today. Making payments by assignment involved going in person to the bank. The banker wrote the transfer in his journal at the customer's dictation, so to speak. In principle, law, but this rule required the presence of both the assignor and the assignee was often disregarded in practice. Bank transfers were frequently made on the strength of an order given by the debtor alone, without the creditor being present. According to a case decided by the Bruges municipal court, payment by book transfer was not complete, however, unless the creditor declared himself satisfied with this mode of settlement.